Bone health in women with breast cancer. (2nd November 2019) - Ramchand, S. K.; Cheung, Y. M.; Grossmann, M.
Abstract: Women with early, estrogen receptor-positive breast cancer are treated with adjuvant endocrine therapy, using aromatase inhibitors or selective estradiol receptor modulators such as tamoxifen, to deprive breast tissue from the deleterious effects of estradiol action, hence improving long-term prognosis. Aromatase inhibitors and, in premenopausal women, tamoxifen accelerate bone loss and increase fracture risk. Therefore, all women commencing endocrine therapy need a targeted work-up to assess the baseline fracture risk, and monitoring of bone health during endocrine therapy should be individualized based on this baseline risk. While high-level evidence specific to early breast cancer is lacking, non-pharmacologic measures to maintain optimal bone health such as weight-bearing exercise and calcium and vitamin D sufficiency should be implemented in all women. Antiresorptive treatment should be initiated in all women with preexisting fragility fractures (including vertebral morphometric fractures) and should be considered in women with areal bone mineral density (BMD) T -scores < −2.0 (or Z -scores in women aged <50 years) or those experiencing rapid bone loss (≥5% per year), taking into consideration the baseline BMD and other risk factors for fracture. Further clinical trial evidence is required to provide definitive guidance regarding criteria to initiate antiresorptive treatment, choice of agents, and duration of treatment, taking into account potential oncologic benefits of antiresorptive therapy on breast cancer-related outcomes.